Nicotinamide Promotes Formation of Retinal Organoids From Human Pluripotent Stem Cells via Enhanced Neural Cell Fate Commitment - Regent, Florian; Batz, Zachary; Kelley, Ryan A.; Gieser, Linn; Swaroop, Anand; Chen, Holly Y.; Li, Tiansen (Frontiers in Cellular Neuroscience, 2022)
Retinal organoids (ROs) derived from human pluripotent stem cells (hPSCs) recapitulate key features of retinogenesis and provide a promising platform to study retinal development and disease in a human context. Although multiple protocols are currently in use, hPSCs exhibit tremendous variability in differentiation efficiency, with some cell lines consistently yielding few or even no ROs, limiting their utility in research. We report here that early nicotinamide treatment significantly improves RO yield across 8 hPSC lines from different donors, including some that would otherwise fail to generate a meaningful number of ROs. NAM treatment promotes neural commitment of hPSCs at the expense of non-neural ectodermal cell fate, which in turn increases eye field progenitor generation. Further analysis suggested that this effect is partially mediated through inhibition of BMP signaling. Our data encourage a broader use of human ROs for disease modeling applications that require the use of multiple patient-specific cell lines.